New Constituents from Gymnocarpos decander - Bechlem, Houria; Mencherini, Teresa; Bouheroum, Mohamed; Benayache, Samir; Cotugno, Roberta; Braca, Alessandra; De Tommasi, Nunziatina (Planta Medica, 2017)
The phytochemical investigation of Gymnocarpos decander aerial parts extract afforded two new saponins, 3-O-β-D-glucuronopyranosyl-2β,3β,16α,23-tetrahydroxyolean-12-en-28-O-β-D-apiofuranosyl-(1 → 3)-β-D-xylopyranosyl-(1 → 4)-α-L-rhamnopyranosyl-(1 → 2)-α-L-arabinopyranosyl ester (1), 3-O-β-D-glucuronopyranosyl-2β,3β,16α-trihydroxyolean-12-en-28-O-α-L-rhamnopyranosyl-(1 → 3)-β-D-xylopyranosyl-(1 → 4)-α-L-rhamnopyranosyl-(1 → 2)-α-L-arabinopyranosyl ester (2), and three new flavonol glycosides, isorhamnetin 3-O-2′′′′-O-acetyl−β-D-xylopyranosyl-(1 → 6)-[β-D-apiofuranosyl-(1 → 2)]-β-D-glucopyranoside (3), isorhamnetin 3-O-2‴-O-acetyl−β-D-xylopyranosyl-(1 → 6)-β-D-glucopyranoside (4), and quercetin 3-O-2‴-O-acetyl−β-D-xylopyranosyl-(1 → 6)-β-D-glucopyranoside (5), together with three known compounds. Their structures were determined by spectroscopic methods including 1D and 2D NMR analysis and high-resolution mass spectrometry. The new isolates were investigated for their potential cytotoxic activity on three cancer cell lines. Compounds 1 and 2 showed moderate antiproliferative activity.
Keywords: Gymnocarpos decander; Caryophyllaceae; triterpenoid saponins; flavonol glycosides; cytotoxicity